#TITLE_ALTERNATIVE# - LINDA LARASATI (NIM : 103 10 021); Pembimbing : Dr. Hesti Retno Tri Wulandari, PRISCILLA
This work builds directly from Mantz et al. (2014) as a partial reconstruction to study the properties of dark energy using NASA-ChandraÃ‚Â’s X-ray observations of galaxy clusters. The main data set employed here consists of measured gas fractions (𝑓𝑔𝑎𝑠) from 40 X-ray luminous, massive, dynamically relaxed galaxy clusters spanning the redshift range 0.078 < z < 1.063. Because galaxy clusters are the most massive gravitationally bound structures in the universe, we can assume that their baryon fractions represent a good sample of the cosmic baryon fraction. Several simulations have indicated that the value of gas fraction, as a dominant contributor of baryonic matter in a cluster, tends to be redshift independent. This is also supported by X-ray observations. From this assumption, cosmological parameters constraints are determined using MCMC method via CosmoMC software for several cosmological models, especially for different dark energy models: (1) ΛCDM, (2) constant- 𝑤, (3) evolving−𝑤(z). The combination of gas fraction data set with several external data (e.g. CMB, SN Ia, and BAO) is used to produce a tighter constraint. Contribution of the gas fraction data gives about 11% reductions in uncertainty values. The constraint results of today's equation of state parameter (𝑤0) are generally consistent with a value close to -1 (Λ). However, the uncertainty range of those values still give possibilities for other dark energy models, such as phantom field or quintessence, to be considered. Meanwhile, the results from ΩΛ constraint generally conclude that around 70% of the universe constitutes of dark energy.